THE MEANING OF VERB FALLING WITHIN BALINESE LANGUAGE SUBTYPE HAPPEN-MOVE: AN APPROACH OF NATURAL SEMANTIC METALANGUAGE - Sari Setiawan, Luh Gde Inten Purnama (LITERA : Jurnal Bahasa Dan Sastra, 2020)
ABSTRACTEvery language has its characteristic that diffentiates it from others. The Balinese languageis one of the many languages in Indonesia that is still is use among the native speakers inBali. This article primarily aims at analyzing the lexicons of the verb â€˜happenâ€™ which havethe representative meaning of â€˜fallingâ€™ within Balinese language. The data was collectedfrom Balinese by direct observation through recording and note-taking. The data wereanalyzed qualitatively by applying the theory of Natural Semantic Metalanguage. NaturalSemantic Metalanguage was used to analyse the data since it is an invaluable descriptivetool for the analysis and contrastive study of meaning-related phenomena in all languages.The result of this study showed that there are several process verb lexicons â€˜fallingâ€ inBalinese language: mageledag, ngetel, aas, and macemplung. The findings indicate thatlexicons â€˜fallingâ€™ in the Balinese language has several different lexicons based on the entityand the process within them.Keyword: Verb falling, Natural Semantic Metalanguage, Balinese languageABSTRAKSetiap bahasa memiliki karakteristiknya sendiri yang membuat bahasa tersebut berbedasatu dengan yang lainnya. Bahasa Bali merupakan salah satu dari sekian banyaknyabahasa daerah yang secara aktif masih di gunakan oleh penutur aslinya. Penelitian inibertujuan untuk menganalisa leksikon-leksikon dengan dasar verba â€˜terjadiâ€™ yang memilikimakna â€œjatuhâ€ dalam bahasa Bali. Metode pengambilan data dilakukan denganmewawancarai dan mencatat percakapan dengan penutur asli bahasa Bali. Data dalampenelitian ini dianalisa melalui metode kualitatif dengan menggunakan pendekatanmetabahasa semantik alami yang dapat mengurai makna-makna kecil dari setiap leksikonbermakna â€˜jatuhâ€™ dalam bahasa Bali. Hasil dari penelitian ini menunjukkan adanyabeberapa leksikon yang merujuk pada satu makna â€˜jatuhâ€™ antara lain mageledag, ngetel,aas, dan macemplung. Hasil penelitian menunjukan bahwa leksikon-leksikon â€˜jatuhâ€™ dalamBahasa Bali memiliki perbedaan leksikon berdasarkan wujud dan proses pemakaian maknatersebut.Kata Kunci: verba â€˜jatuhâ€™, Metabahasa Semantik Alami, Bahasa Bali